Social transfers and poverty in middle- and high-income countries – A global perspective. (April 2016) - Ferrarini, Tommy; Nelson, Kenneth; Palme, Joakim
This study investigates an old question that has re-emerged in social policymaking and in analyses of global social development: to what extent does targeting and size of social transfers matter for poverty? Using multilevel logistic regression and Cross-National Data Center in Luxembourg (LIS) income data for 40 middle- and high-income countries, we show that the size of transfer income has greater explanatory value for cross-country differences in poverty than the degree of targeting of transfer income. The results are remarkably robust in terms of estimated individual-level and country-level compositional and confounding factors.